空间凸轮过渡圆弧的设计及尖角过渡过切现象分析 - 褚辉生 (Jixie chuandong)
The paper analyses affecting on movement law of special cam that by transition arc radius of special cam,we conclude that transition arc radius should be great than half of groove’s width and that sharp-angled transition will bring excessive removal while NC-machining.